Reading Film as a Text: Hermeneutics of Suspicion from Film the Joneses - Anam, Rifqi Khairul (Dekonstruksi, 2025)
Film, as a form of mass communication, is fundamentally a textual representation that communicates a specific message. The act of watching a film is fundamentally equivalent to perusing a book, as both mediums are designed to communicate a message. Analyzing a film involves the engagement of our entire repertoire of memories, which serves as the foundation for interpreting its significance. The objective of this research is to illuminate the significance of covert marketing and the hazards it presents by examining the material object of the film The Joneses through the lens of Paul Ricoeur's hermeneutics of suspicion and employing a content analysis approach. Film "The Joneses" portrays a seemingly flawless family with appealing adolescent children and a high socioeconomic status as an ideal. It is, however, disclosed that they are in fact covert marketing agents who engage in stealth marketing. Stealth marketing is an unscrupulous marketing strategy that exploits the consumer's subconscious, obscuring the fact that they are being approached with a product. This form of marketing deceives consumers into believing that they actually need the item, despite the fact that its practical value is superfluous. Instead, the item functions as a representation of one's social status. Therefore, stealth marketing contributes to the perpetuation of a consumer-driven society, in which consumption is employed to demonstrate one's identity and novelty.